(untitled) (Journal of International Crisis and Risk Communication Research, 2019)
This study proposed a defi nition of perceived crisis severity and created a valid and reliable scale to measure the construct following Churchill’s scale development procedure. The proposed scale, after rigorous pilot testing and exploratory and confi rmatory factor analysis, contains 3 factors with 12 items. This study discusses potential applications of the developed measures and provides future research directions.